Acute Coronary Syndrome as a Teachable Moment for Smoking Cessation. (16th December 2013) - Tofler, Geoffrey H.; May, Robin; Bartrop, Roger; Kirkness, Ann; Glinatsis, Helen; de Burgh, Simon
ABSTRACT Introduction: Although the teachable moment has been recognised as an important contributor to behaviour change, its role in smoking cessation merits further investigation. Aim: We prospectively evaluated 116 patients hospitalised with a suspected acute coronary syndrome in two tertiary referral hospitals. The patients comprised 84 men and 32 women, aged 54.2 ± 8.5 years, and the final diagnosis was myocardial infarction in 90 and angina in 26. Results/Findings: At one month, the self-reported quit rate was 65%, maintained to 61% at 12 months. The quit rate was greater at one and 12 months for those diagnosed with myocardial infarction (70% and 67%) compared with those who had angina (46% and 40%), p<0.05. The strongest motivators for quitting were the heart attack and the consequences of the diagnosis. Of those who quit at 1 month, 77% did so without additional aids. Conclusions: Hospitalisation with an acute coronary syndrome is associated with a high quit rate, and the diagnosis of heart attack with its potential consequences represents a strong teachable moment to stop smoking. The findings support further investigation of the teachable moment to aid in smoking cessation.